Considerations on the mechanism used for applying disciplinary sanctions - Adrian, Nicolescu (Technium Social Sciences Journal, 2020)
The essential role of the disciplinary sanctions is similar to that of the criminal sanctions and consists in the future prevention of facts that could affect the labor relations, which result from the individual employment contract concluded between the employer and the employee according to the law. In the current labor law, the legislator left within the employer the power to sanction the employee in the situation in which he violates the discipline of work, but this possibility is not a non-binding one, but one in strict compliance with the legislation in force. For the correct application of the disciplinary sanctions, that is to say, without prejudice to the rights of the employee, no disciplinary sanction, except the written warning, can be disposed of before carrying out the preliminary disciplinary investigation. Once the employee’s guilt has been ascertained and after carrying out the preliminary investigation in accordance with the imposed procedures, the employer is able to establish the disciplinary sanction taking into account the following legal criteria, such as the circumstances in which the act was committed, the degree of the employee’s guilt and, not in last, the general behavior at work. The disciplinary sanction, in general, in order to be implemented by the employer, must be outlined by means of a written one, respectively by a sanctioning decision that is communicated to the employee so that he is aware its provisions, and in certain cases it can challenge an eventual abusive behavior of the employer. Through this administrative instrument there are clearly described the deviations of the employee from the labor norms.